A sustainable [P6, 6, 6, 14]2[OPBOA]-based separation process of rare earth and transition metal in waste NiMH battery. (1st January 2021) - Su, Xiang; Xie, Wenqi; Sun, Xiaoqi
Graphical abstract: Highlights: Mild conditions and no organic diluent were used to recovery NiMH battery. Higher separation efficiency of RE vs. transition metal could be reached. NaCl solution could be used to remove transition metal without the loss of RE. Larger particle of RE stripping precipitate could be formed by Na2 CO3 solution. [P6, 6, 6, 14 ]2 [OPBOA] and NaCl solution could be recycled. Abstract: The separation of rare earth (RE) and transition metals is a critical step in the recycling of nickel-metal hydride (NiMH) battery. From the point of environmental and practical issues, an ionic liquid (IL) [trihexyl(tetradecyl)phosphonium]2 [2, 2' -(1, 2-phenylenebis(oxy))dioctanoate] ([P6, 6, 6, 14 ]2 [OPBOA]) was newly synthesized for the separation of RE from transition metals in NiMH batteries leachate. The separation factors of βNd/Co and βNd/Ni could arrive at 5.2 × 10 3 and 5.4 × 10 3, respectively. Meanwhile, the extracted Ni(II) and Co(II) could be effectively scrubbed and stripped by 0.5 mol/L sodium chloride (NaCl) solution without loss of RE. The loaded Nd(III) in [P6, 6, 6, 14 ]2 [OPBOA] could be quantitatively stripped by 0.014 mol/L hydrochloric acid (HCl), 0.016 mol/L sodium oxalate (Na2 C2 O4 ) or 0.022 mol/L sodium carbonate (Na2 CO3 ). [P6, 6, 6, 14 ]2 [OPBOA] could be recycled without regeneration when Na2 C2 O4 and Na2 CO3 were used as stripping agents and larger precipitated particle size could be obtained by low-concentration Na2 CO3 solution. In the process of separating rare earth and transition metal from NiMH battery, even to handle 500 mL feed solution, the recovery efficiency and purity of RE in NiMH batteries could still reach more than 96.4% and 99.8 wt% by using NaCl and Na2 CO3 for stripping, respectively. As characterized by XRD, the recovered RE oxides could be easily obtained by calcinations.